การพัฒนาสูตรอาหารฟังก์ชั่น : เครื่องดื่มมะขามผงฟู่และเยลลี่มะขาม - พจนา แก้วทินกร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Tamarind pulp is considered a mild laxative. This thesis developed functional foods in the formula of tamarind effervescent beverage and tamarind jelly from spray dried tamarind powder. Fruit pulps of Tamarindus indica L. cultivar sour type, "Priao" from Nakhon Ratchasima were extracted with deionized water and were concentrated under reduced pressure in rotary evaporator. The tamarind concentrate was mixed with 10, 20, 30 and 40 %w/w maltodextrin and transformed into tamarind powder by spray-drying technique. The mixture was pumped into a atomizer at the rate of 3.0 ml/min. The temperature of inlet and outlet air were 130℃ and 90℃, respectively and the pressure was 6 bars. For tamarind effervescent powder beverage, various combinations of sodium bicarbonate and citric acid were investigated. The best physical properties combination was chosen for further study of the replacement of sugar with following sweeteners, sucrose, fructose and swizsi®. Five formulas were chosen for the evaluation of the physical properties and the acceptances test. The formula that contained 0.26 g sodium bicarbonate, 0.20 g citric acid and 4.00 g sucrose was most acceptable and showed the best physical properties. The stability of the effervescent powder was studied for 30 days at room temperature and at 2-8℃. It was found that moisture content, pH and tartaric content differed. For tamarind jelly, various combinations of tamarind powder, sucrose and pectin were investigated. The gel formation and physical properties were evaluated. The best physical properties combination was chosen for further study of the replacement of sugar with following sweeteners, sucrose and fructose. Four formulas were chose for the acceptances test. The formula that contains 6% tamarind powder, 40% sucrose and 1% pectin was most acceptable and showed the best physical properties.